2004
DOI: 10.1128/iai.72.6.3478-3488.2004
|View full text |Cite
|
Sign up to set email alerts
|

Interaction ofBlastomyces dermatitidis,Sporothrix schenckii, andHistoplasma capsulatumwithAcanthamoeba castellanii

Abstract: Several dimorphic fungi are important human pathogens, but the origin and maintenance of virulence in these organisms is enigmatic, since an interaction with a mammalian host is not a requisite for fungal survival. Recently, Cryptococcus neoformans was shown to interact with macrophages, slime molds, and amoebae in a similar manner, suggesting that fungal pathogenic strategies may arise from environmental interactions with phagocytic microorganisms. In this study, we examined the interactions of three dimorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
3
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 39 publications
3
98
3
1
Order By: Relevance
“…pathogenicity between the phylogenetically disparate mammals and insects; [43][44][45] this finding has potential evolutionary implications as fungal virulence may have evolved as a countermeasure to environmental predation by non-vertebrate organisms that feed on fungi. 7,46 Consistent with this notion, Histoplasma capsulatum and Cryptococcus neoformans strains were reported to enhance their virulence after passage through amoebas; 27,28 thus, whether and how interaction of fungi with Drosophila or Galleria results in modulation of the expression of virulence factors merits investigation.…”
Section: Fungal Virulence Studiesmentioning
confidence: 62%
“…pathogenicity between the phylogenetically disparate mammals and insects; [43][44][45] this finding has potential evolutionary implications as fungal virulence may have evolved as a countermeasure to environmental predation by non-vertebrate organisms that feed on fungi. 7,46 Consistent with this notion, Histoplasma capsulatum and Cryptococcus neoformans strains were reported to enhance their virulence after passage through amoebas; 27,28 thus, whether and how interaction of fungi with Drosophila or Galleria results in modulation of the expression of virulence factors merits investigation.…”
Section: Fungal Virulence Studiesmentioning
confidence: 62%
“…While these pathogenic fungi survived and killed the amoebas, a nonpathogenic fungus such as Saccharomyces cerevisiae and the human-adapted fungus Candida albicans were killed by the protozoan. Furthermore, it was also observed that an avirulent strain of H.capsulatum recovered its virulence after being co-cultured with the amoeba Acanthamoeba castellani [28].…”
Section: Origin and Maintenance Of P Brasiliensis' Virulencementioning
confidence: 93%
“…The main attraction of these ideas resides in the possibility of testing them experimentally, for example, by putting together the fungus with some phagocytic soil amoebas in the same tube. That is what has been done, not just with C. neoformans, but also with the dimorphic fungi B. dermatitidis, H. capsulatum, and S. schenckii [28]. While these pathogenic fungi survived and killed the amoebas, a nonpathogenic fungus such as Saccharomyces cerevisiae and the human-adapted fungus Candida albicans were killed by the protozoan.…”
Section: Origin and Maintenance Of P Brasiliensis' Virulencementioning
confidence: 95%
“…Because APMV's fibrils are important for its adhesion to A. castellanii cells, which seems to occur through viral interactions with GlcNAc and mannose, we investigated if the giant virus could adhere to other organisms that display one or more of these glycans (as well as their polymers, chitin and peptidoglycan) on their structures. Considering that the entry of APMV into amoebae occurs via phagocytosis, the association of the virus with organisms present in aquatic macro-or microniches (bacteria, fungi, and aquatic arthropods) may increase the chances of an encounter between the virus and its natural host, because interactions between amoebae and bacterial biofilms, insects, and microcommunities containing fungal species have already been described (18)(19)(20). To test this hypothesis, viral particles were incubated with distinct representatives of the microbial world, such as fungi (which have mannose and chitin on their cell walls) and both Gram-positive and Gram-negative bacteria (which have peptidoglycans on their cell walls).…”
Section: Resultsmentioning
confidence: 99%